2015
DOI: 10.1364/oe.23.011453
|View full text |Cite
|
Sign up to set email alerts
|

WS_2 as a saturable absorber for ultrafast photonic applications of mode-locked and Q-switched lasers

Abstract: Two-dimensional (2D) nanomaterials, especially the transition metal sulfide semiconductors, have drawn great interests due to their potential applications in viable photonic and optoelectronic devices. In this work, 2D tungsten disulfide (WS2) based saturable absorber (SA) for ultrafast photonic applications was demonstrated. WS2 nanosheets were prepared using liquid-phase exfoliation method and embedded in polyvinyl alcohol (PVA) thin film for the practical usage. Saturable absorption was discovered in the WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
152
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(157 citation statements)
references
References 45 publications
4
152
1
Order By: Relevance
“…Several groups also found that WS 2 nanosheets exhibit nonlinear saturable absorption property at 1.55 µm, and observed soliton mode-locking or Q-switching operations in erbium-doped fiber (EDF) lasers [28][29][30]. The aforementioned studies were mainly concentrated on the anomalous-dispersion regime, and mode-locking operation based on WS 2 SA has not been reported in normaldispersion fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups also found that WS 2 nanosheets exhibit nonlinear saturable absorption property at 1.55 µm, and observed soliton mode-locking or Q-switching operations in erbium-doped fiber (EDF) lasers [28][29][30]. The aforementioned studies were mainly concentrated on the anomalous-dispersion regime, and mode-locking operation based on WS 2 SA has not been reported in normaldispersion fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, WS 2 [42,50,66,67] and WSe 2 [42] have been demonstrated in passively Q-switched Er:fibre lasers. Additionally, a single MoSe 2 SA was used to Q-switch Yb, Er and Tm-doped fibre lasers [55].…”
Section: Q-switched Fibre Lasersmentioning
confidence: 99%
“…The laser produced 800 ps pulses at a 6.6 MHz pulse repetition frequency, with an average output power of 9.3 mW [33]. Further work through cavity dispersion engineering resulted in sub-picosecond pulse generation [39,45,66,73], down to 637 fs [45]. These ultrafast lasers operated in the net anomalous dispersion regime, generating solitons.…”
Section: Mode-locked Fibre Lasersmentioning
confidence: 99%
“…DMS and DS were formed from opposite direction in a fiber laser, respectively [37]. In addition, Q-switched pulse and mode-locked pulse can be achieved through WS 2 saturable absorber (SA) in a fiber laser, respectively [38]. Q-switched mode-locked pulse was acquired in Tm: LiLuF 4 laser [39] and erbium-doped fiber (EDF) laser based on gold nanorod-PVA [40].…”
Section: Introductionmentioning
confidence: 99%